2020
DOI: 10.5812/pedinfect.101632
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C Infections Among Pediatric Patients with Sickle Cell Disease at a Tertiary Hospital in Nigeria

Abstract: Background: The frequent use of blood products for patients with sickle cell disease (SCD) may put them at risk of infecting with hepatitis virus infections, especially if such blood products are not properly screened. Hepatitis B and C infections (HBV and HCV, respectively) may result in cirrhosis and liver cell cancer. Objectives: This study determined the prevalence of HBV and HCV infections among pediatric patients with sickle cell disease in comparison to matched controls at the Ekiti State University Tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Ekiti study reported very low prevalence of 1%, reason was that most of the study 44 group had received hepatitis B vaccination. 44 HBsAg was found only in those not vaccinated. The prevalence obtained from this study is however lower than that obtained in various studies among 39,41 39 SCA patients from Benin.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Ekiti study reported very low prevalence of 1%, reason was that most of the study 44 group had received hepatitis B vaccination. 44 HBsAg was found only in those not vaccinated. The prevalence obtained from this study is however lower than that obtained in various studies among 39,41 39 SCA patients from Benin.…”
Section: Discussionmentioning
confidence: 93%
“…There are few studies on the prevalence of HBV infection among SCA children, most of which were [37][38][39][40][41][42][43][44] inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that some studies in Africa have shown a higher prevalence of HBV and HCV among patients with SCD, 59–61 we did not corroborate this in our study. Studies in Nigeria which compared the seroprevalence rates of HBV and HCV among patients with SCD, with and without a history of transfusion with healthy age‐ and sex‐matched controls, did not show a significant difference in prevalence rate of these viral markers among both groups 62–64 . However, a study from the northern part of Nigeria (Zaria) in 2002 reported one patient (one of 55; 1.8%) who was HIV‐seropositive on chronic transfusion 51 .…”
Section: Discussionmentioning
confidence: 98%
“…Studies in Nigeria which compared the seroprevalence rates of HBV and HCV among patients with SCD, with and without a history of transfusion with healthy age-and sex-matched controls, did not show a significant difference in prevalence rate of these viral markers among both groups. [62][63][64] However, a study from the northern part of Nigeria (Zaria) in 2002 reported one patient (one of 55; 1.8%) who was HIV-seropositive on chronic transfusion. 51 However, in the present study, none of the children with SCD on regular or episodic blood transfusion were seropositive for any of the viral TTIs (Table 1), even though the median number of RBC transfusions was 16.5 units for those on regular transfusions (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In Ekiti state, prevalence rates of 3.9% and 6.2% were reported amongst pregnant women and adults, respectively [5,6]. Also, amongst children and adolescents, varying seroprevalences have been reported from diferent parts of Nigeria [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%